2016
DOI: 10.1016/j.chb.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ experience of offline and online risks: Separate and joint propensities

Abstract: Adolescence is a period of increased risk experience and ever more often these occur online.The current study aims to investigate whether adolescents' online and offline risk experiences are driven by the same general propensity to risks. Data from a representative study of N = 19,406 (50% girls) internet-using 11-16 year olds (M = 13.54, SD = 1.68) youth in Europe were subjected to the current analyses. Three confirmatory factor analyses were applied to measures of offline and online risk experiences (five ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…While both cyber- and face-to-face victimization peak at an age period that is known for a peak in anti-social behavior due to the influence of delinquent peers (Moffitt, 1993), the current study shows that beyond peers’ behaviors, the general prevalence of criminal behaviors in the cultural and regional proximity does correspond with bullying victimization rates. This appears to be the case for face-to-face bullying as well as for cyberbullying, confirming previous notions that adolescent risk experiences, whether offline or online, are linked by common underlying factors (Görzig, 2016). Given the marginal significance, however, these results and interpretations do need to be considered with caution.…”
Section: Discussionsupporting
confidence: 86%
“…While both cyber- and face-to-face victimization peak at an age period that is known for a peak in anti-social behavior due to the influence of delinquent peers (Moffitt, 1993), the current study shows that beyond peers’ behaviors, the general prevalence of criminal behaviors in the cultural and regional proximity does correspond with bullying victimization rates. This appears to be the case for face-to-face bullying as well as for cyberbullying, confirming previous notions that adolescent risk experiences, whether offline or online, are linked by common underlying factors (Görzig, 2016). Given the marginal significance, however, these results and interpretations do need to be considered with caution.…”
Section: Discussionsupporting
confidence: 86%
“…International survey-based research has reported that anywhere from 9 to 24% of adolescents have experienced bullying through SNS sites, and 88% have witnessed bullying towards SNS users (Livingstone, Haddon, Görzig, & Olafsson 2011;Görzig, 2016;Patchin & Hinduja, 2012;Bastiaensens et al, 2014). Cyber-bullying victimization among adolescents has been linked to negative mental health and physical health outcomes, such as depression, poor self-esteem, emotional distress, and in more extreme cases, episodes of self-harm and suicide attempts (Bastiaensens et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current finding is in line with other research showing that those who belong to minority groups are more vulnerable to cyberhate and cyberbullying victimization (Blaya, 2019;Tynes, 2015). Similar to the relations between cyberbullying and bullying these findings highlight associations between offline and online contexts (Blaya et al, 2020;Görzig, 2016b). Further research is needed toward a better understanding of the processes that lead individuals to be involved in online hate as well as offline discrimination and to include both types of victimization in intervention programmes.…”
Section: Discussionmentioning
confidence: 69%